Prevalence and determinants of violence against health care in the metropolitan city of Peshawar: a cross sectional study - Muhammad Naseem Khan; Zia Ul Haq; Mirwais Khan; Sadia Wali; Faryal Baddia; Shaista Rasul; Salman Khan; Maciej Polkowski; Jessica Yohana Ramirez-Mendoza (BMC, 2021)
Abstract Background Violence against healthcare personnel is a major public health problem. Healthcare personnel are at the frontline dealing with people in stressful and unpredictable situations. Therefore, this study was conducted to determine the prevalence and associated factors of violence against health care personnel. Methods A cross sectional study was conducted in the district Peshawar. Healthcare personnel from public and private sectors working in both the primary and tertiary levels of healthcare were invited to participate. Violence was assessed through a structured questionnaire previously used in Pakistan and was defined as experiencing and/or witnessing any form of violence in the last 12 months. Mental health was assessed through the General Health Questionnaire. Logistic regression was used to estimate the association of violence against healthcare personnel with psychological distress and demographic characteristics. Data entry and analysis were conducted in STATA 14. Results A total of 842 healthcare personnel participated in the study. The prevalence of violence experienced and/or witnessed by healthcare personnel in Peshawar was 51%. Verbal violence remained the predominant form of violence and almost half of the healthcare personnel (45%) were exposed to it. A quarter of the respondents (24%) reported physical violence alone or in combination with other forms of violence. In almost two third of the incidents the perpetrators were either attendants, relatives or the patients. The emergency unit and wards within healthcare facilities were the most common places where violent events took place. The major factors responsible for the violent incidents were communication failure, unreasonable expectations and perceived substandard care. No uniform policy/procedure existed to manage the incidents and the healthcare personnel adopted different responses in the wake of violent events targeting health care. Working in public healthcare facilities and having a larger number of co-workers/colleagues significantly increased the risk of violence in the healthcare settings while being a paramedic significantly reduced the risk as compared to physicians. Conclusions Violence against healthcare personnel is a serious public health issue and the prevalence is quite high. A holistic effort is needed by all stakeholders including healthcare community, the administration, lawmakers, law enforcement, civil society, and international organizations.